La agonía de la ética y la antropología. Notas a partir del pensamiento de Manuel Marzal - Mujica Bermúdez, Luis (Pontificia Universidad Católica del Perú. Fondo Editorial, 2008)
This paper is divided into three different sections. The first sectionconsiders the annotations of Manuel Marzal, an anthropologist and professor at the Pontificia Universidad Católica del Perú who passed away in the year 2005, about ethics as a concern coming form an anthropological perspective. Secondly, the article presents a balance on the bibliography about this issue, contrasting Marzal’s preoccupations with the latest bibliography, mainly Peruvian, which deals with ethics and morals in an explicit or implicit sort of way. Finally, living in the post-political violence and Commission for Truth and Reconciliation Final Report period, in order to make an anthropology on ethics one has to consider two methodological references and four dimensions to explore the people’s behaviors in relationto others. The methodological references require a «dense description » on morality to try to understand the simplicity of the relations and investigate and reflect on a multidisciplinary perspective. The four dimensions in which to explore ethics are daily life, religiosity, economics and politics.

El artículo consta de tres partes. En la primera parte considera las anotaciones de Manuel Marzal, antropólogo y profesor de Pontificia Universidad Católica del Perú, fallecido en el año 2005, sobre el tema de la ética como preocupación temática desde la antropología. En segundo lugar, se hace una revisión —a modo de balance bibliográfico— sobre el mismo tema contrastando las preocupaciones de Marzal con la producción de los últimos años, sobre todo en el área peruana, realizada por diversos antropólogos quienes han abordado de forma explícita o implícita el tema ético o moral. Finalmente, en un contexto de postviolencia política y del Informe Final de la Comisión de la Verdad y Reconciliación, se propone que para haceruna antropología de la ética en estos tiempos debe considerarse dos referencias metodológicas y cuatro dimensiones para explorar la conducta de las personas en relación con otras. Las referencias metodológicas requieren de una «densa descripción» de las moralidades para tratar de entender la simplicidad de las relaciones e investigar y reflexionar el tema en una perspectiva multidisciplinar.
The agony of ethics and anthropology. Notes from Manuel Marzal's thought
Keywords: Etica; Moralidad; Agonía; Política; Economía; Vida cotidiana; Marzal; https://purl.org/pe-repo/ocde/ford#5.04.03